AI Cloud Presenting Tool Attracts Senior High School Teacher Experience - Leon A. Abdillah; Hikmah A. Adam; Elvin L. Hadisaputro; Sugeng Budi Rahardjo; Arina Ashfa Fikriya (Direktorat Riset dan Pengabdian Pada Masyarakat (DRPM) Universitas Bina Darma, 2026)
Online presentation tools have become essential resources for increasing teaching and learning experiences. This study examines senior high school teachers' experiences using Canva, a well-known online presentation tool, in their classroom activities. The purpose of this article is to investigate how the incorporation and effective use of a cloud presenting tool can transform senior high school teaching practices by improving teacher experiences and fostering innovative technological-based pedagogical approaches. A mixed-methods methodology was used in the research, integrating quantitative data from a thorough User Experience Questionnaire and observation insights gleaned from open-ended survey questions. A total of 81 participants experienced teachers from different schools. The UEQ data's quantitative analysis found extremely favorable user experience ratings across a number of parameters, showing that most teachers perceive Canva to be attractive, stimulating, and dependable. The qualitative findings added to our understanding of teachers' experiences by highlighting the particular elements they valued and the areas that needed improvement. However, the survey also revealed some difficulties that teachers encounter, including the early learning curve and sporadic technological issues. These findings highlight how crucial it is to give educators the right instruction and assistance so they can reap the potential advantages of adopting online presenting tools like Canva. Overall, the study's contribution to instructional technology can assist improve educational quality and students' digital abilities and competences. The study's findings give guidance for educational institutions and policymakers seeking to successfully integrate technology in the classroom to improve teaching tactics, boost student engagement, and improve learning outcomes. The technology appears to have successfully captured these educators' interest and usage, showing its potential value and significance in high school education.